Kajian Peranan Indeks Indeks Kesehatan, Indeks Pendidikan, Dan Indeks Daya Beli Terhadap Tingkat Kemiskinan Kabupaten Sidoarjo Tahun 2010-2023 - Parikesit Penangsang; Pramita Studiviany; Adiati Trihastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Regional economic development needs to be planned and the benchmark is economic growth. Development in developing countries still prioritizes unemployment and poverty. Development in Indonesia to date still focuses on efforts to reduce the unemployment rate or open up job opportunities to reduce poverty. The level of poverty can be measured through the HDI (Human Development Index) which has three main indicators, namely health indicators, education level and economic indicators. There are many factors that hinder the development of an area, one of which is the high poverty rate. The problems of unemployment and poverty are still major issues that never end. Sidoarjo Regency has a decreasing number of poor people starting from 2021 at 137 people, in 2022 at 125 people and in 2023 at 119 people from a population of 2,238,069 people in 2021, 2,266,533 people in 2022, 1,996,825 people in 2023. The causes of poverty are the large number of children who have dropped out of school, limited public services (schools) which are difficult to reach, difficulty in getting health costs and the difficulty of people getting the necessities of life such as clothing, food and shelter. The aim of making a Study on the Role of the Health Index, Education Index and Purchasing Power Index on the Poverty Level of Sidoarjo Regency for 2010-2023, is to see the contribution of these three indices to changes in poverty levels in Sidoarjo Regency, both directly and indirectly, which will have an impact on change in poverty (number of poor people). It is hoped that this research can be used as consideration for Sidoarjo district in future community development so that they can live prosperously.